Design optimization of oil pan thermoelectric generator to recover waste heat from internal combustion engines. (1st June 2020) - Aljaghtham, Mutabe; Celik, Emrah
Abstract: Nearly 75% of fuel energy is rejected to the environment and ultimately becomes waste heat in motor vehicles. To recover some of this waste heat and enhance fuel efficiency, thermoelectric energy generators (TEGs) possess high potential. We investigated the feasibility of utilizing TEGs in terms of oil pans to recover waste heat generated in internal combustion engines. Hot oil at the top surface of TEG and air cooling at the bottom create a high thermal gradient for the thermoelectric conversion. An extensive multi-physics simulation framework was introduced to accurately simulate conversion of heat into electricity taking into account thermoelectricity, joule heating, heat conduction and turbulent air cooling. To maximize the thermoelectric power, dimensions and the total number of thermoelectric modules were optimized under different oil pan geometries and driving conditions. Our simulations show that the maximum power density of 5.77 kW m −2 is achieved with multi-step oil pan geometry under a 76 °C temperature difference between the hot and cold sides. This power density surpassed those reported for the previous, conventional (exhaust and radiator) thermoelectric applications and indicated that harvesting thermal energy from combustion engines using oil pans is a feasible energy recovery methodology to enhance fuel efficiency in automotive vehicles. Highlights: Waste heat recovery is limited to exhaust systems in automotive applications. Thermoelectric modules can be used in engine oil pans as robust energy harvesters. Multiphysics numerical simulations can predict thermoelectric energy harvesting. Kilowatt range power is generated at high efficiency by multi-step engine oil pan. Modular, thermoelectric oil pan can save significant fuel without any water-cooling system.